Pilus PilA of the naturally competent HACEK group pathogen Aggregatibacter actinomycetemcomitans stimulates human leukocytes and interacts with both DNA and proinflammatory cytokines. (December 2022) - Vahvelainen, Nelli; Bozkurt, Esra; Maula, Terhi; Johansson, Anders; Pöllänen, Marja T.; Ihalin, Riikka
Abstract: Each HACEK group pathogen, which can cause infective endocarditis, expresses type IVa pili. The type IVa major pilin PilA plays a role in bacterial colonization, virulence, twitching motility, and the uptake of extracellular DNA. The type IV prepilin homolog PilA of the periodontal pathogen A. actinomycetemcomitans (AaPilA) is linked to DNA uptake and natural competence. Our aim was to investigate the virulence properties and immunogenic potential of AaPilA. Since Neisseria meningitidis PilE, which shares sequence similarity with AaPilA, participates in sequestering host cytokines, we examined the ability of AaPilA to interact with various cytokines. Moreover, we investigated the structural characteristics of AaPilA with molecular modeling. AaPilA was conserved among A. actinomycetemcomitans strains. One of the 18 different natural variants, PilAD7S, is present in naturally competent strains. This variant interacted with DNA and bound interleukin (IL)-8 and tumor necrosis factor (TNF)-α. Specific anti-AaPilA antibodies were present in A. actinomycetemcomitans- positive periodontitis patient sera, and the production of reactive oxygen species from human neutrophils was less effectively induced by the Δ pilA mutant than by the wild-type strains. However, AaPilA did not stimulate human macrophages to produce proinflammatory cytokines, nor was it cytotoxic. The results strengthen our earlier hypothesis that the DNA uptake machinery of A. actinomycetemcomitans is involved in the sequestration of inflammatory cytokines. Furthermore, AaPilA stimulates host immune cells, such as B cells and neutrophils, making it a potential virulence factor. Highlights: Bacterial type IVa pilus homolog PilA stimulates human leukocytes. Type IVa pilus homolog PilA interacts with host cytokines. Conserved A. actinomycetemcomitans pilus PilA is a potential virulence factor.